Investigating the Efficacy of Vaccination Against Hepatitis B in Families of Infected Patients: in a Hyperendemic Area of Iran - motahareh Mahi-Birjand; ali reza Shabani; arezo Khosrojerdi; efat Alemzadeh; samira Elhamirad; masoud Ziaee (Iranian South Medical Journal)
Background: Hepatitis B virus (HBV) is recognized as a leading cause of liver disease globally, resulting in chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. With an estimated 296 million people infected worldwide and an annual mortality rate of around 820,000, hepatitis B presents a significant public health challenge. The virus is transmitted through blood and bodily fluids, with particular significance given to vertical transmission (from parents to children) and horizontal transmission (between spouses), especially in hyperendemic regions. Materials and Methods: This retrospective descriptive study examined the prevalence of hepatitis B among families in Esfandiar village, a hyperendemic area in Iran. The research involved 133 individuals who tested positive for HBsAg and 199 of their family members. Key demographic characteristics, infection factors (HbsAg status), and antibody titers were analyzed. Results: The results indicated that 15.4% of the spouses and 5% of the children of the patients were HBsAg-positive, while 21% of their children had a history of infection with HBV. Furthermore, vaccination history revealed that only 0.9% of vaccinated individuals were HBsAg-positive, compared to a striking 40% positivity rate among the unvaccinated. Conclusion: These findings highlight the critical role of familial transmission of hepatitis B, particularly between couples and from parents to children. They also underscore the importance of vaccination and health education in curbing the spread of this disease.